2021
DOI: 10.1051/0004-6361/202140460
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz instability and collapse of a twisted magnetic null point with anisotropic viscosity

Abstract: Context. Magnetic null points are associated with high-energy coronal phenomena such as solar flares and are often sites of reconnection and particle acceleration. Dynamic twisting of a magnetic null point can generate a Kelvin-Helmholtz instability (KHI) within its fan plane and can instigate spine-fan reconnection and an associated collapse of the null point under continued twisting. Aims. This article aims to compare the effects of isotropic and anisotropic viscosity in simulations of the KHI and collapse i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…For brevity, we will refer to this model of viscosity as 'the switching model '. In Quinn et al ( 2020c ) andSimitev ( 2021 ), we implemented the switching model as a module for the widely used general MHD code Lare3d (Arber et al 2001 ), and demonstrated significant effects of anisotropic viscosity on the development of the non-linear MHD kink instability and the Kelvin-Helmholtz instability . More generally , the interest in anisotropic viscosity stems from the open question of which heating mechanism (viscous or Ohmic) is dominant in the solar corona (Klimchuk 2006 ), an important facet of solving the coronal heating problem.…”
mentioning
confidence: 99%
“…For brevity, we will refer to this model of viscosity as 'the switching model '. In Quinn et al ( 2020c ) andSimitev ( 2021 ), we implemented the switching model as a module for the widely used general MHD code Lare3d (Arber et al 2001 ), and demonstrated significant effects of anisotropic viscosity on the development of the non-linear MHD kink instability and the Kelvin-Helmholtz instability . More generally , the interest in anisotropic viscosity stems from the open question of which heating mechanism (viscous or Ohmic) is dominant in the solar corona (Klimchuk 2006 ), an important facet of solving the coronal heating problem.…”
mentioning
confidence: 99%
“…Expression ( 11) is identical to the strong field approximation of the general anisotropic viscosity tensor derived by Braginskii (Braginskii 1965). Expressions ( 9) and ( 11) arise as asymptotic limits of the more general switching model used in our earlier works (MacTaggart et al 2017;Quinn et al 2020cQuinn et al , 2021 which, includes both isotropic and anisotropic contributions and can switch gradually between them depending on the strength of the magnetic field at a given spaciotemporal location. For example, in the vicinity of a null point where the magnetic field becomes weak the isotropic viscosity contribution becomes dominant in the switching model.…”
Section: Mathematical Formulation and Numerical Setupmentioning
confidence: 99%
“…The non-dimensionalisation of equations ( 7) is identical to that used in our earlier works (Quinn et al 2020c(Quinn et al , 2021 and in reference (Arber et al 2001) that describes the code Lare3d we use for numerical solution, see further below. A typical magnetic field strength šµ 0 , density šœŒ 0 and length scale šæ 0 are chosen and the other variables non-dimensionalised appropriately.…”
Section: Mathematical Formulation and Numerical Setupmentioning
confidence: 99%
See 2 more Smart Citations